The devil and the sacred in English drama, 1350-1642 - Cox, John D., 1945- (Cambridge University Press, 2000)
John Cox tells the intriguing story of stage devils from their earliest appearance in English plays to the closing of the theatres by parliamentary order in 1642. The book spans both medieval and Renaissance drama from the Mystery cycles through to plays by Greene, Marlowe, Shakespeare, Jonson, Middleton and Davenant.
Includes index.
Keywords: English drama -- Early modern and Elizabethan, 1500-1600 -- History and criticism.; Devil in literature.; English drama -- 17th century -- History and criticism.; English drama -- To 1500 -- History and criticism.; Christian drama, English -- History and criticism.; Christianity and literature -- England -- History.; Good and evil in literature.; Holy, The, in literature.; Théâtre anglais -- 16e siècle -- Histoire et critique.; Démon dans la littérature.; Théâtre anglais -- 17e siècle -- Histoire et critique.; Théâtre anglais -- Jusqu'à 1500 -- Histoire et critique.; Christianisme et littérature -- Angleterre -- Histoire.; Sacré dans la littérature.; DRAMA -- English, Irish, Scottish, Welsh.; Christian drama, English; Christianity and literature; Devil in literature; English drama; English drama -- Early modern and Elizabethan; Good and evil in literature; Holy, The, in literature; England; Das Heilige; Teufel -- Motiv; Drama; Toneelstukken.; Engels.; Duivel.; Het heilige.; Englisch.; 18.05 English literature.; Evil in literature.; Christianity and literature -- Great Britain -- History.; To 1699; Electronic books.; Criticism, interpretation, etc.; History